Study of the Congruence between Accounting Numbers and Stock Market Variables through Comprehensive Income: Empirical Evidence for Romania Companies Quoted On the Regulated Market - Marilena Mironiuc; Maria Carmen Huian (Journal of Accounting and Management Information Systems (JAMIS), 2016)
This research is a hypothetical-deductive study whose purpose is to analyse if, in the case of non-financial companies quoted on the regulated market of the Bucharest Stock Exchange, the reporting of the information on Comprehensive Income is relevant for the investors. The present paper also aims to identify several degrees of value relevance for Comprehensive Income, in direct correlation with the informational value of certain stock return indicators for the investors. For the analysed population and for the time horizon taken into account, we noticed that Other Comprehensive Income per Share, the variance of Other Comprehensive Income per Share and the Differences from the revaluation of tangible and intangible assets in relation to the investment per share are expressive predictors for the investors on the financial market. The ranking of the effects of reporting the information on Other Comprehensive Income expresses the most visible relevance in Goodwill Per Share, then in the Share Price and, thirdly, in Total Shareholder Return.
Keywords: M41; 650; value relevance; comprehensive income; stock market price; goodwill per share; total shareholder return